Meat microbiota: A conceptual review - MAK Azad; MM Rahman; MAK Azad (Meat Research, 2022)
Changing life style and food habit increase concern about meat and meat products serving as vehicles of food-borne cluster of micro-organisms. Major and highly publicized outbreaks of food-borne disease have been associated with consumption of contaminated meat and have led to increased interest in meat safety among public health agencies, regulatory authorities, researchers, industry and consumers. Thus, authorities in most developed countries have established regulatory requirements aimed at improving the hygienic status of the meat supply. Characteristics of meats, types and sources of microbiota, the main factors governing microbial proliferation and their detrimental effects, prevention measures to spoilage meat and meat products, and finally the reference values for different counting methods are needed to establish regulatory initiatives. Thus, the present review will discuss each and every point of the above.